An investigation into the learning environments of blended delivery (e-learning and classroom) in a tertiary environment - Skelton, David J. E. (Curtin University, 2007)
This thesis describes research investigating the learning environment of tertiary students undertaking their studies through a mixture of online learning management systems and traditional tertiary classroom delivery. A review of the literature examined traditional learning environments, pure online virtual environments and more recent literature pertaining to a blended environment. The examination of student and staff perceptions of learning environments in different contexts served to generate recommendations to help tertiary teachers optimise online and traditional teaching practices within a mixed-mode environment. Students' experiences of their learning environment were discovered through quantitative and qualitative methods. Quantitative data on students' experiences were gathered by using an adapted version of the Web-based Learning Environment Instrument (WEBLEI). Qualitative data on students' experiences were collected by discussion questions added to the WEBLEI survey. Qualitative data on the use of online and blended learning environment experiences by tertiary staff were gathered by email and supplementary interviews. The study synthesised results from these multiple sources within a tertiary institute environment and made recommendations and gave insight into optimal blended learning environments within the tertiary sector. Overall, the study provided a perspective on the psychology and strategic view of the learning environment for the future tertiary institute.